Kemampuan Pemahaman Konsep Matematika Siswa Melalui Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) pada Pembelajaran Matematika di Kelas VIII SMP PGRI 1 Betung - Muhammad Yogi Ramadhan; Eka Yanuarti (ARITHMETIC: Academic Journal of Math, 2020)
This study aims to determine the ability of students to understand mathematical concepts through the Indonesian Realistic Mathematics Education (PMRI) approach to learning mathematics in class VIII of SMP PGRI 1 Betung. This research is a "quasi experiment" category of one shot case study. In this study, there was only one sample class, namely the class that became the experimental class, namely class VIII.5 consisting of 35 students, which was carried out without a control class or comparison class. The data collection technique used in this research is the test method, and documentation. The results of this study indicate that the students' ability to understand mathematical concepts after the application of the Indonesian Realistic Mathematics Education Approach (PMRI) at SMP PGRI Betung is categorized as good, this is shown by the results of the average score. -The average final test of students' ability to understand mathematical concepts was 76.8.